Beboelse i landskabet - en analyse af bebyggelsernes placering i landskabet fra jernalder til middelalder i området omrking Eltang Vig - Marienlund, Casper (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
This paper examines the location of the excavated farms and settlements in the landscape surrounding the tunnel valley of Eltang Vig from the Iron Age to the Middle Ages. The main bulk of the archaeological evidence comes from several campaigns at the archaeological sites of Banggård II, Eltang, and Marielyst from 2014 to 2019, and their connection to older excavated sites. The landscape in this area was affected significantly during the ice age. The terrain changes rapidly, and the landscape is characterised by high hills and tunnel valleys, closely connected to The Little Belt. The large, investigated area of approximately 123 ha offers a great opportunity to study the archaeological area and to focus on the location of the buildings in the landscape on a greater scale. Although large parts of the landscape have not been archaeologically examined, the survey indicates that some areas were more densely populated than others during different periods of time, which could indicate that the role of the landscape and the use of it changed over time, due to aspects such as local agriculture, trade, and security.